Talk Is Cheap. - Blau, J. (IEEE spectrum)
The first-generation of low-cost handsets are now being delivered in developing countries such as Bangladesh, India, Nigeria and Yemen. These supercheap phones have been stripped of everything except simple telephony and text messaging functions and feature single-chip designs, slimmed down software and price tags of US 40 dollars and lower. Handset manufacturers believe that it is their social responsibility to connect many of the less fortunate of the world at a price they can afford. At the same time, they see new opportunities in these less-developed regions as they struggle to expand in the heavily saturated advanced industrial markets